Hidrovia e desenvolvimento regional: estudo dos projetos de desenvolvimento dos vales do Tietê e Paraná no Estado de São Paulo - Lorenzo, Helena Carvalho de [UNESP]; Queda, Oriowaldo; Correa, Mario Augusto (My University, 2012)
"This paper aims to examine three regional development plans proposed for the region of the valleys of rivers Tietê and Paraná: Rail Project (ISCO, 1994), the Development Plan (CESP, 1996) and Máster Plan (ADTP, 1996). The interest in conducting the study relies on the possibility that it may contribute to the debate on the reshaping of public policy and style necessary to establish a new pattern of regional development in the country"

Este artigo tem por objetivo analisar três planos de desenvolvimento regional propostos para a região dos vales dos rios Tietê e Paraná: o Projeto Calha (CITP, 1994), o Plano de Fomento (CESP, 1996) e o Plano Máster (ADTP, 1996). O interesse em realizar o estudo apoia-se na possibilidade de que o mesmo possa contribuir para a reflexão sobre a reformulação e estilo das políticas públicas necessárias para estabelecer um novo padrão de desenvolvimento regional no país.
Waterway and regional development: a study of development projects of the valleys of Tietê and Paraná in the state of São Paulo
Keywords: Regional Planning; Waterway and regional development; Development projects of the Tietê and Paraná valleys; Planejamento regional; Hidrovia e desenvolvimento regional; Projetos de desenvolvimento dos vales do Tietê e Paraná